Attributions for physical activity in very old adults: predicting everyday physical activity and mortality risk. Issue 2 (1st February 2019) - Parker, Patti C.; Chipperfield, Judith G.; Perry, Raymond P.; Hamm, Jeremy M.; Hoppmann, Christiane A.
Abstract: Objectives: Although physical activity is recognised as a health-promoting behaviour for older adults, notable barriers exist that may reduce physical activity in this age group. Limited research has explored causal beliefs (attributions) as a barrier to physical activity. Our study assessed associations between older adults' attributions about physical activity and objective health outcomes.Methods: We examined the role of attributions as a predictor of everyday physical activity (EPA) and subsequent mortality risk over a 10-year period (2006–2016) in a sample of older adults ( M age = 87, N = 261).Results: OLS and Cox proportional hazard regression analyses revealed older adults who endorsed more internal and uncontrollable attributions for limited activity (physical incapacity) when feeling unwell had lower subsequent EPA ( β = −0.18), and higher 10-year mortality risk ( HR = 1.46). Other attributions with different dimensional properties (e.g. internal and controllable) were not associated with EPA or mortality.Discussion: Findings suggest that causal beliefs older adults have about their physical activity can influence their future behaviour and longevity. Psychological treatments designed to discourage maladaptive attributional thinking for older populations who face barriers to physical activity may be an important avenue for future research.